2005
DOI: 10.1002/lsm.20137
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial on low level laser therapy (LLLT) in the treatment of osteoarthritis (OA) of the hand

Abstract: LLLT is no better than placebo at reducing pain, morning stiffness, or improving functional status for OA-hand patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
94
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 34 publications
2
94
1
3
Order By: Relevance
“…They found that there were no significant differences in pain quality between the active treatment group and the control group. 40 This may be attributed to differences in nature of arthritic changes and number of sessions of treatment. 40 Another different factor for contrast is the difference between the gallium-aluminum-arsenide diode laser used in their work 40 and the gallium-arsenide diode laser used in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that there were no significant differences in pain quality between the active treatment group and the control group. 40 This may be attributed to differences in nature of arthritic changes and number of sessions of treatment. 40 Another different factor for contrast is the difference between the gallium-aluminum-arsenide diode laser used in their work 40 and the gallium-arsenide diode laser used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…40 This may be attributed to differences in nature of arthritic changes and number of sessions of treatment. 40 Another different factor for contrast is the difference between the gallium-aluminum-arsenide diode laser used in their work 40 and the gallium-arsenide diode laser used in this study. The contradictions in the literature of LLLT benefits may be attributed to variations in treatment parameters by LLLT, such as wavelength, power, energy density, number, and duration of treatment, size of exposure area, and method Laser Therapy on Chronic Knee Osteoarthritis of Elders of laser administration.…”
Section: Discussionmentioning
confidence: 99%
“…Several progressive and degenerative diseases have been effectively treated by means of LLLT (12,38,39) , but there is controversy regarding the results from studies analyzing pain and function among patients with knee OA, mainly because of the variations in the methods used. In the present clinical trial, care was taken to follow the WALT recommendations (40) regarding how to conduct a clinical trial with LLLT, and care was taken to report all the parameters used in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has an analgesic effect, although the mechanisms through which this occurs remain uncertain. The suggested mechanisms include: increased mitochondrial ATP and tissue oxygenation, increased levels of neurotransmitters implicated in pain modulation (such as serotonin) and anti-inflammatory effects (5,12) .…”
mentioning
confidence: 99%
“…Other authors have written more extensively on this topic. 9,18,19 The primary purpose of this article was to present a case of MCP joint OA associated with a manual labor occupation and, in doing so, familiarize chiropractors with the so-called Missouri metacarpal syndrome. 15 This article also serves to remind the chiropractic physician of the key differentials of MCP arthropathy, namely, hemochromatosis and CPPD crystal deposition disease.…”
Section: Discussionmentioning
confidence: 99%